Assembly of two-dimensional materials - Soo, Wee Liong (2019)
Research and development of two-dimensional hexagonal Boron Nitride (h-BN) have progressed rapidly due to its unsurpassed mechanical and thermal properties which leads to the discovery of potential uses in coatings, filtrations and energy storage applications. To enable the full potential of those intrinsic properties and realise its potential applications, few-layer h-BN has to be extracted from bulk h-BN powder. In this project, a study of isolating and assembling few-layer through exfoliation and vacuum assisted filtration respectively is conducted. More specifically, on improving the dispersability of h-BN in water through liquid-exfoliation and to perform assembly of 2D few-layer h-BN into 3D membrane with the exfoliated solutions. The aim is to support the investigation in potential applications of h-BN membrane for ionic sieving. Herein, dispersion of pristine h-BN in ethanol-water mixture is analysed, ethanol to water ratio of 55:45 is employed for dispersion. An alternative method examined is rendering h-BN hydrophilic by treating pristine h-BN with hydroxyl functional group to improve dispersability. With both pristine and treated h-BN solutions, dispersion is further improved by performing exfoliation under ultrasonic conditions. Dispersion of both pristine and hydroxyl functionalized h-BN are illustrated in this study. Thereafter, vacuum filtration method is employed to construct a membrane of few-layer h-BN. Lastly, the membranes are examined for ionic sieving capability of seawater.